PENGARUH PROFITABILITAS, KEPUTUSAN INVESTASI, KEBIJAKAN HUTANG DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Property, Real estate dan Building Contrusction yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2015) - Muhammad Ridho; Azwir Nasir; Volta Diyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The high of firm value is one purpose of the company. The firm value of a company is the perception investors about the success rate of the company that are often associated with stock price. This research was purposed to find out the affect of profitability, investment decision, debt policy and firm size on firm value of property, real estate and building construction company listed on the stock exchange in 2014-2015. The population were 55 companies and a sample are 42 companies. The analytical type use associative analysis with the analyze tool used was classic assumption, multiple linear test, hypothesis. The result of the study found that 1) Profitability has significant effect on the firm value 2) Investment decision has significant effect on the firm value 3) Debt policy has affected on firm value 4) Firm size has no effect on firm value. The percentage of influence of profitability, investment decision, debt policy and firm size on firm value is 21,2%.Keyword : Profitability, Investment Decision, Debt Policy, Firm Size And Firm Value